MANOPENG SEBAGAI AKTUALISASI JEJAK PANJI PADA ETNIS BANJAR - Sari, Putri Yunita Permata Kumala (JURNAL PAKARENA, 2025)
Manopeng is a rite tradition that belongs to the juriyat panopengan (descendants of the masked tradition) in Banyiur Luar Village, Basirih Subdistrict, Banjarmasin City, South Kalimantan. The people who are ethnically Banjar always carry out their annual family routine with the aim of family gatherings, cleaning the village or repelling reinforcements, and treating non-medical diseases. This tradition arose because of the inclusion of the Panji culture in the Banjar community of South Kalimantan. The banners that spread to Southeast Asia were brought by Majapahit and South Kalimantan was no exception. This article informs the traces of the Panji culture which is actualized in the Manopeng tradition in the Banjar ethnic community. The search was carried out using a qualitative descriptive method to photograph field phenomena. The masks used as ritual media at the Manopeng ceremony are masks of the Panji epic puppet with various mask characters, such as: Panji Mask, Gunung Sari Mask, Kelana Mask, Patih Mask, Tumenggung Mask, Coat of Arms Sari, Reflective Mask, Tambam Mask, Sangkala Mask and additional characters such as the 7 Angel Masks. The procession that was carried out from cleaning the mask, tapung bargaining, to dancing the mask illustrates that the Panji cultural traces are actualized in the culture of the Banjar people who are assimilated with the local culture as one of the ancestral heritage which is still maintained by the supporting community to this day.